Circular labor migration and subsistence agriculture: a case of the Iban in West Kalimantan, Indonesia - Wadley, R.L. (1997)
This dissertation is an analysis of circular labor migration and its effect on subsistence agriculture among the Iban of West Kalimantan, Indonesia. Based on lengthy field research, it focuses on the intersection of Iban economy, demography, and social organization, including the nature of male labor migration, household composition, the labor exchange system, the role of women in farming and in Iban society generally, and the nature of forest-fallow farming. In this remote area of Indonesian Borneo, Iban subsistence revolves around the cultivation of rice in hill, floodplain, and swamp swiddens. Hill swiddens, cut from long-fallowed forest, are particularly important. In addition, cash cropping, especially of rubber, supplements subsistence farming. However, the lack of good prices and local markets for cash crops results in high frequencies of male wage-labor migration. Circular labor migration refers to a pattern in which people seek work away from home but return after months or years. Among these Iban men, it is largely international, to jobs they find across the border in Malaysia and Brunei. There the wages are higher and the currencies more stable, and men’s earnings can be quite substantial by Indonesian standards. Wages are used to pay for consumer goods, subsistence foods when crops fail, and schooling for children and younger siblings. Chronic male absence negatively affects the home community in a number of ways, including increased workloads on women in farming and domestic activities. However, as this study shows, women are more involved in agriculture regardless of the presence of men, and the absence of men does not negatively affect a household’s ability to produce sufficient rice for itself. Likewise, male absence does not lead to male-poor households farming shorter (and less labor-demanding) fallows, which have been assumed to result in poorer yields. Factors that account for this situation include the widespread use of chainsaws in felling forest for farming, a functioning labor exchange system, household structure and composition, and women’s control of their reproduction.